1992
DOI: 10.1136/gut.33.8.1126
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxaemia and serum tumour necrosis factor as prognostic markers in severe acute pancreatitis.

Abstract: Endotoxaemia and circulating tumour necrosis factor are important prognostic factors in severe sepsis and are implicated in the pathogenesis of septic shock. Because clinical and pathological features in acute pancreatitis are similar to septic shock this study sought to determine whether endotoxin and tumour necrosis factor were prognostic factors in 38 patients with prognostically severe acute pancreatitis. Endotoxaemia, present in 19/37 (51%) patients on day 1, was more common in nonsurvivors than survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(79 citation statements)
references
References 24 publications
1
77
1
Order By: Relevance
“…S1A). Serum levels of TNF, a main causal factor of sepsis and endotoxemia (10)(11)(12)(13)(14)(15), had the peak at 1 h after LPS treatment to the same levels in WT and Rag2 −/− mice (Fig. S1A).…”
Section: T Cells Have a Protective Role In Lps Endotoxemia By Down-mentioning
confidence: 96%
“…S1A). Serum levels of TNF, a main causal factor of sepsis and endotoxemia (10)(11)(12)(13)(14)(15), had the peak at 1 h after LPS treatment to the same levels in WT and Rag2 −/− mice (Fig. S1A).…”
Section: T Cells Have a Protective Role In Lps Endotoxemia By Down-mentioning
confidence: 96%
“…Moore, Silliman, and others (52)(53)(54) have shown that PAF is a primary agent responsible for neutrophil priming in human trauma victims. In contrast, LPS and TNF␣ are the likely priming agents in acute pancreatitis (55,56), as well as in many patients with sepsis (57)(58)(59)(60)(61), and these agents have been directly implicated in causing acute lung injury (62)(63)(64)(65) and ischemia-induced acute renal failure (66).…”
mentioning
confidence: 99%
“…TNF-· has been shown to be an important initiator of local and systemic damage occurring in AP and the blocking of the action of this cytokine has been shown to delay the onset of AP (9). Additionally, serum TNF-· levels have been found to be correlated with the severity of AP in humans (28). IL-1ß has been shown to be a significant cytokine for the development of AP and the inhibition of its production has been shown to decrease the severity of AP (29,30).…”
Section: Discussionmentioning
confidence: 99%